Maqashid al-Shariah as a Paradigm of Contemporary Islamic Legal Theory - Zulfikri; Sofwan Tambunan; Zaini Munawir; Ahmad Senang (ISNU Sumatera Utara, 2025)
Maqashid al-shariah is a fundamental concept in Islamic law that explains the purpose of establishing sharia to realize human welfare. In the development of modern Islamic legal thought, this concept is increasingly gaining attention as a methodological approach in understanding Islamic law more contextually. This study aims to analyze the basic concept of maqashid al-shariah, the development of its thought in the tradition of classical scholars, and its relevance as a paradigm in the development of contemporary Islamic legal theory. This study uses a qualitative approach with a literature study method through a conceptual analysis of classical and modern literature on maqashid al-shariah. The results of the study indicate that the concept of maqashid al-shariah has been formulated systematically by scholars of the usul fiqh, especially Abu Hamid Al-Ghazali and Abu Ishaq Al-Shatibi, who emphasize that the main purpose of sharia is to maintain human welfare through the protection of five basic needs. In the development of modern thought, this concept was then expanded by thinkers such as Muhammad al-Tahir Ibn Ashur and Yusuf al-Qaradawi so that maqashid was not only understood as a theory in the principles of fiqh, but also as a methodological paradigm in formulating more contextual Islamic law. In conclusion, maqashid al-shariah has significant relevance as a paradigm in the development of contemporary Islamic legal theory because it is able to explain the relationship between the text of the sharia and the beneficial objectives to be realized. Therefore, the maqashid approach needs to continue to be developed in the study of Islamic law so that it can make a more adaptive contribution to the dynamics of modern society.